Evaluation of somaclonal variants under field condition for the varietal improvement of strawberry (Fragaria × Ananassa Duch.) in Bangladesh - Ara, T; Ogita, S; Hossain, MM; Islam, AKMR (Journal of Bio-Science, 2018)
The present study was conducted to standardize a suitable protocol for varietal improvement of strawberry through somaclonal variation using in vitro techniques. Leaf segments of seven strawberry varieties viz. AOG, JP-2. JP-3, Camarosa, Sweet Charly, Giant Mountain and Festival were used for callus induction and shoot regeneration. Regenerated plantlets were planted into the field to evaluate their morphological characters, yield contributing characters, response to fungal diseases and summer overcoming potentiality (%) of the transplanted plantlets compare with their parents and data were recorded. Among the seven strawberry varieties AOG was found to be the most responsive genotype for callus induction, shoot regeneration and rooting. A total of 40-45 somaclonal variants from each of the tested varieties were established and maintained in the field and were considered as R0 plants. There were no somaclones found resistance to fungal diseases but someone’s, specially AOG SC 3 showed better tolerance than the donor plants. Comparing with donor plants and other somaclones AOG SC 3 was found better summer overcoming potentiality. It can be acceptable commercially if the good characters exhibited are transmitted through generations or could be used in future breeding programme for the improvement of strawberry varieties in Bangladesh. J. bio-sci. 24: 19-32, 2016